Peran Pendidikan Kewarganegaraan Bagi Pembentukan Civic Virtue Dalam Masyarkat Multikultural Menurut William A. Galston: Sebuah Tinjauan dari Perspektif Filsafat Politik - Gabriel Junior Ell (Jurnal Seri Mitra (Refleksi Ilmiah - Pastoral), 2023)
William Arthur Galston is one of the contemporary political philosophers who pays attention to issues of modern citizenship, specifically the reality of a pluralistic society. His great concern for the reality of a pluralistic society is especially apparent in his writings on multiculturalism. Because Galston's thoughts generally depart from the facts of a pluralistic modern society. That is why he thinks a civic virtue concept  is needed in a multicultural society. Galston understands civic virtue as the ability of each person to develop self-quality but also must be able to work together with others and have priority to support the public interest rather than personal or group interests with the aim that democracy can develop properly. So that every citizen understands and owns civic virtue Education is needed, more precisely citizenship education. That means civics education has an important role because of the means or instruments needed by citizens and members of society to have civic virtues. For that reason, Galston emphasized that Citizenship Education can and even absolutely must be implemented in a liberal democratic country. With the help of the method of description and analysis, this thesis attempts to explain the role of citizenship education in developing civic virtue as an important component in a multicultural society according to Galston. The description is divided into three parts: The first part discusses the course of life Galston. The second part explains the concept of civic virtue according to Galston and the third part explains the role of civics education.